2016
DOI: 10.3109/14397595.2016.1149267
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of two interferon-γ releasing assays to detect past tuberculosis infections in Japanese rheumatoid arthritis patients

Abstract: Both assays were equally useful with high specificities, but may falsely identify past tuberculosis infection owing to low sensitivities. In patients with low total and CD4-positive lymphocyte counts, both assays might give higher rates of false negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In RA patients receiving methotrexate, a positive correlation has been observed between CD4 and CD8 lymphocyte counts with the positive results of QFT and T-Spot tests. 94 Similar to the previous study, one evaluation in Japan showed in RA patients underlying treatment with anti-TNF agents, higher positive results of QFT-Plus and T-Spot tests were associated with CD4 T-cell >650/μl and CD8 T-cell >400/ μl compared to other groups and the rate of negative results increase with CD4 and CD8 T-cell less than these values. 78 As a result, in RA patients receiving DMARD or anti-TNF agents, reduction in lymphocyte count and activity can cause unreliable IGRA results, so assessment of TB just based on the IFN-γ value may not be an appropriate approach.…”
Section: False Negative Tb Test Results In Rasupporting
confidence: 84%
See 1 more Smart Citation
“…In RA patients receiving methotrexate, a positive correlation has been observed between CD4 and CD8 lymphocyte counts with the positive results of QFT and T-Spot tests. 94 Similar to the previous study, one evaluation in Japan showed in RA patients underlying treatment with anti-TNF agents, higher positive results of QFT-Plus and T-Spot tests were associated with CD4 T-cell >650/μl and CD8 T-cell >400/ μl compared to other groups and the rate of negative results increase with CD4 and CD8 T-cell less than these values. 78 As a result, in RA patients receiving DMARD or anti-TNF agents, reduction in lymphocyte count and activity can cause unreliable IGRA results, so assessment of TB just based on the IFN-γ value may not be an appropriate approach.…”
Section: False Negative Tb Test Results In Rasupporting
confidence: 84%
“…Another important finding is that monitoring LTBI in patients receiving DMARD or anti‐TNF agents can lead to false‐negative IGRA results. In RA patients receiving methotrexate, a positive correlation has been observed between CD4 and CD8 lymphocyte counts with the positive results of QFT and T‐Spot tests 94 . Similar to the previous study, one evaluation in Japan showed in RA patients underlying treatment with anti‐TNF agents, higher positive results of QFT‐Plus and T‐Spot tests were associated with CD4 T‐cell >650/μl and CD8 T‐cell >400/μl compared to other groups and the rate of negative results increase with CD4 and CD8 T‐cell less than these values 78 .…”
Section: Screening For Latent Tb Infection In Ramentioning
confidence: 93%
“…Although T-SPOT assay has limited specificity for the diagnosis of ATB in high endemic countries, this assay has been broadly used for detection of MTB infection worldwide. Except for the limited specificity, a decreased sensitivity of T-SPOT assay in immunocompromised patients has been noticed (Pan et al, 2015;Dittrich and Lehmann, 2012;Iwagaitsu et al, 2016). The interpretation of T-SPOT data sometimes can become ambiguous, especially when spot numbers in antigen-containing wells are low in immunocompromised patients (Dittrich and Lehmann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be that host immune status affects the results of T-SPOT assay. Some factors, such as age, over-weight, longer periods of illness before hospitalization and immunosuppressive therapy may contribute to reduced or even negative T-SPOT results (Hadaya et al, 2013;Cai et al, 2014;Pan et al, 2015;Dittrich and Lehmann, 2012;Iwagaitsu et al, 2016). Therefore, interpretation of T-SPOT results would become ambiguous especially in patients with immunocompromised status (Dittrich and Lehmann, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Disagreement between TST and IGRA has led some authors to suggest that both tests should be performed in high-risk patients (travelling or coming from endemic regions) and/or in countries with high TB-burden 39 49 51. On the other hand, Quantiferon and enzyme-linked immunosorbent spot (ELISpot), two IGRA test platforms, appear to have good concordance52–55 (table 2). Several studies have shown that IGRA display a better performance compared with TST, having better sensitivity and specificity and being associated more closely with TB risk factors 13 14 17 19 25 30 55–57.…”
Section: Resultsmentioning
confidence: 99%